The Effect of Transformational Leadership on Employee Performance Through Organizational Citizenship Behavior in Industrial Revolution 4.0 - Hidayat, Samsul; Wirawan, Ida Bagus; Adam, Subagyo; Trisliatanto, Dimas Agung; Abdullah, Muhammad Ridhuan Tony Lim (Politeknik APP Jakarta, 2022)
The transformation of government organizations should be characterized by the development of visionary leadership transformation that was measured at various levels of leadership in government organizations, this was needed to ensure that every innovation developed could provide value-added service quality, harmonized the vision and internal environment which had balanced with the ability to respond to environmental changes external which moved quickly in this era of the Industrial Revolution 4.0. The purpose of this study was to analyze and examined the effect of transformational leadership on employee performance through organizational citizenship behavior in the Bulog of Indonesia for facing the industrial revolution era 4.0. The results of this study concluded that organizational citizenship behavior was an intervening variable in the effect of transformational leadership on employee performance in the Bulog of Indonesia facing the era of Industrial Revolution 4.0.